GPCR-specific autoantibody signatures are associated with physiological and pathological immune homeostasis. Issue 1 (December 2018) - Cabral-Marques, Otavio; Marques, Alexandre; Giil, Lasse; Vito, Roberta; Rademacher, Judith; Günther, Jeannine; Lange, Tanja; Humrich, Jens; Klapa, Sebastian; Schinke, Susanne; Schimke, Lena; Marschner, Gabriele; et al.
Abstract Autoantibodies have been associated with autoimmune diseases. However, studies have identified autoantibodies in healthy donors (HD) who do not develop autoimmune disorders. Here we provide evidence of a network of immunoglobulin G (IgG) autoantibodies targeting G protein-coupled receptors (GPCR) in HD compared to patients with systemic sclerosis, Alzheimer's disease, and ovarian cancer. Sex, age and pathological conditions affect autoantibody correlation and hierarchical clustering signatures, yet many of the correlations are shared across all groups, indicating alterations to homeostasis. Furthermore, we identify relationships between autoantibodies targeting structurally and functionally related molecules, such as vascular, neuronal or chemokine receptors. Finally, autoantibodies targeting the endothelin receptor type A (EDNRA) exhibit chemotactic activity, as demonstrated by neutrophil migration toward HD-IgG in an EDNRA-dependent manner and in the direction of IgG from EDNRA-immunized mice. Our data characterizing the in vivo signatures of anti-GPCR autoantibodies thus suggest that they are a physiological part of the immune system. Autoantibodies are implicated in autoimmunity, but may also be present in healthy individuals. Here the authors find that the autoantibody specificity signatures against various G protein-coupled receptors are associated with multiple parameters, including disease states, to imply a physiological function in maintaining immune homeostasis.